Wong Saloh Saw Pin of Master Lamduan Suwannaphukham Chorkeaw Band in Phrae Province - Mungpa, Watcharaporn; Pornprasit, Kumkom (Rangsit Music Journal, 2023)
This study is a qualitative research using data collected from fieldwork during the year 2019-2020. The aim is to study the biography, ways to play musical instrument, vocal melody, and music melody. The research process includes data collection, data study, data analysis and conclusion. It is found that Master Lamduan Suwannaphukham is an expert of folk music in Nan province and is a leader of Chorkeaw band. With more than 50 years of experience, she becomes widely famous. Master Lamduan is a disciple of Master Muangdee Dhebprasith from whom she learnt both ritual and performance. Her method of Pin playing mostly involves the major second, the major third and the use of Sabud technique. Her Saloh playing incorporates all intervals and the use of Prom, Kayee and Sabud technique. Master Lamduan generally uses 2 words per 1 bar structure in her lyrics, except in improvisation where it is necessary to use many words. Word stressing usually occurs on the last note of the bar, following the accent of northern dialect. She also uses Sorn Seang technique to emphasize words. Folk music in Nan province mostly uses Uern Technique in 2 cases. The first one is when there are words using Thai high tone and rising tone called Mai Tree and Mai Jattawa. The second case is to connect words between bars, which is mostly used in skeletal melody songs more than fixed melody songs. From studying the songs called Dard Naan, Lublang, Pamatatongtang, Dard Phrae and Japuchiangglang, it is found that the melodies are arranged with 3 Penta centric modes, namely Pengaorbon, Java and Glanghaeb mode.